Daily physical activity of Brazilian carriers of arterial hypertension: a transversal analysis (Colombia Medica, 2017)
Objective:  To describe the profile of the practice of physical activity in the daily life of Brazilian adults with arterial hypertension and to analyze whether the practice performed complies with the recommendations of the World Health Organization.Methods:  Cross-sectional data were obtained from the Surveillance System of Risk Factors and Protection for Chronic Noncommunicable Diseases of 2014, involving 40,853 adults aged 18 years and over in all Brazilian capitals, interviewed by telephone survey.Results: Walking, soccer and water aerobics were the main modalities of exercise and sport practiced. The weekly volume of effort led 35% of practitioners to reach the recommended goal of the World Health Organization. The low weekly frequency of activities stood out among hypertensives who did not reach the goal.Conclusion:  Health services should clarify the need for regularity of physical activity for hypertensive individuals to benefit substantially.